Constitutive Defense Mechanisms Have a Major Role in the Resistance of Woodland Strawberry Leaves Against Botrytis cinerea - Zhao, Yijie; Vlasselaer, Liese; Ribeiro, Bianca; Terzoudis, Konstantinos; Van den Ende, Wim; Hertog, Maarten; Nicolaï, Bart; De Coninck, Barbara (Frontiers in Plant Science, 2022)
The necrotrophic fungus Botrytis cinerea is a major threat to strawberry cultivation worldwide. By screening different F. vesca genotypes for susceptibility to B. cinerea, we identified two genotypes with different resistance levels, a susceptible genotype Fragaria vesca ssp. vesca (Tenno 3, T3) and a moderately resistant genotype F. vesca ssp. vesca (Kreuzkogel 1, K1). These two genotypes were used to identify the molecular basis for the increased resistance of K1 compared to T3. Fungal DNA quantification and microscopic observation of fungal growth in woodland strawberry leaves confirmed that the growth of B. cinerea was restricted during early stages of infection in K1 compared to T3. Gene expression analysis in both genotypes upon B. cinerea inoculation suggested that the restricted growth of B. cinerea was rather due to the constitutive resistance mechanisms of K1 instead of the induction of defense responses. Furthermore, we observed that the amount of total phenolics, total flavonoids, glucose, galactose, citric acid and ascorbic acid correlated positively with higher resistance, while H2O2 and sucrose correlated negatively. Therefore, we propose that K1 leaves are more resistant against B. cinerea compared to T3 leaves, prior to B. cinerea inoculation, due to a lower amount of innate H2O2, which is attributed to a higher level of antioxidants and antioxidant enzymes in K1. To conclude, this study provides important insights into the resistance mechanisms against B. cinerea, which highly depend on the innate antioxidative profile and specialized metabolites of woodland strawberry leaves.